Your medical mind : how to decide what is right for you - Groopman, Jerome E. (Byword Books, 2012)
This book offers advice on making medical decisions inspite of confusing and conflicting information, provides insight into the personal beliefs influencing how choices are made while citing the marketing practices that complicate the process. Making the right medical choices is harder than ever. Whether deciding on a cholesterol drug or choosing a cancer treatment, we are overwhelmed by information from all sides: our doctors' recommendations, dissenting expert opinions, confusing statistics, conflicting media reports, the advice of friends, claims on the Internet, and a never-ending stream of drug company ads. This book shows us how to chart a clear path through this sea of confusion. Both doctor, the authors reveal that each of us has a set of deeply rooted beliefs whose profound influence we may not realize when we make medical decisions. Recognizing our preferences and the external factors that might lead our thinking astray can make a dramatic, even lifesaving, difference in our medical decision making. The authors drew on research and insights from patients, doctors, psychologists, economists, and other experts to help reveal the array of forces that can aid or impede our thinking. Ultinately, this is a chronicle of how ordinary people, landing at a medical crossroads, must decide about care, who should provide it, and for how long. -- From publisher description.